1994
DOI: 10.1071/ar9940529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brassica break crops on the growth and yield of wheat

Abstract: The effect of the Brassica crops, canola and Indian mustard, on the growth and yield of subsequent wheat crops was investigated in field experiments at four sites in southern New South Wales. In all experiments, shoot growth, root growth, disease incidence and water and nitrogen use of wheat following the Brassica crops were compared with wheat following wheat. Linseed and field peas were included as break crops at some sites for comparison. At one site, methyl bromide fumigation was used to investigate break … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
2
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 14 publications
0
62
2
6
Order By: Relevance
“…Channels produced by cover crop roots in the autumn and winter, when soils are relatively moist, may facilitate the penetration of compacted soils by subsequent crop roots in summer when soils are relatively hard and dry (Chen & Weil, 2011;Creswell & Kirkegaard, 1995). Kirkegaard et al (1993) hypothesized that tap-rooted Brassica crops produce channels in the dense subsoil, which were utilized by the subsequent crop to access water and nutrients as well as increase yield, and they reported that in seasons with adequate rainfall, the yield advantage of wheat grown after the Brassica crop was in the range of 15-25% greater compared with a wheat mono-crop which was unlike our research. William and Weil (2004) suggested that roots of summer crops grew following channels created by preceding cover crops which provided lower resistance channels for soybean roots to search for water in the subsoil late in the season during drought thus increasing soybean yields to 200 kg ha -1 and the impacts of preceding cover crops were greatest during severe drought and highly compacted soil conditions.…”
Section: Winter Annual Weed and Corn Response The Following Yearcontrasting
confidence: 65%
“…Channels produced by cover crop roots in the autumn and winter, when soils are relatively moist, may facilitate the penetration of compacted soils by subsequent crop roots in summer when soils are relatively hard and dry (Chen & Weil, 2011;Creswell & Kirkegaard, 1995). Kirkegaard et al (1993) hypothesized that tap-rooted Brassica crops produce channels in the dense subsoil, which were utilized by the subsequent crop to access water and nutrients as well as increase yield, and they reported that in seasons with adequate rainfall, the yield advantage of wheat grown after the Brassica crop was in the range of 15-25% greater compared with a wheat mono-crop which was unlike our research. William and Weil (2004) suggested that roots of summer crops grew following channels created by preceding cover crops which provided lower resistance channels for soybean roots to search for water in the subsoil late in the season during drought thus increasing soybean yields to 200 kg ha -1 and the impacts of preceding cover crops were greatest during severe drought and highly compacted soil conditions.…”
Section: Winter Annual Weed and Corn Response The Following Yearcontrasting
confidence: 65%
“…Regarding nitrogen, it is important to stress the role it plays in the synthesis of chlorophyll and in the assimilative processes that influence root growth and as a consequence trigger a virtuous circle of improved water and nutrient uptake along the soil profile (Kirkegaard et al 1994). Also phosphorus participates in overall plant growth and in particular in root development; it also controls flowering and fruit setting and assimilates translocation and balances the relations between vegetative and reproductive functions of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the bulk of the evidence suggests that NT tends to result in lower crop N concentration. The N content of wheat grain has been reported to be increased (Strong et al 1986;Kirkegaard et al 1994) or not (Vaidyanathan et al 1987) by antecedent broadleaf crops such as field pea or Brassica sp. The influence of crop rotation, and its interaction with tillage, on N and other plant nutrient concentrations in grain and uptake by crops has not been adequately documented.…”
mentioning
confidence: 99%